Nonlinear stability and buckling analysis of composite functionally graded arches subjected to external pressure and temperature loading. (15th November 2019) - Li, Zhaochao; Zheng, Junxing; Zhang, Zhen; He, Hantao
Highlights: The heated FGM arch is pressurized and shows different stability performance from the homogeneous arch. The material is distributed non-uniformly in the cross-section. The analytical solution is derived and verified by the numerical simulation. The thermal rise field increases the upward radial displacement that is beneficial to the buckling pressure. The thermal rise field reduces Young's modulus that is unbeneficial to the buckling pressure. Abstract: This paper investigates the nonlinear stability and buckling behavior of the composite functionally graded material (FGM) arches subjected to pressure and temperature loadings. By introducing an admissible displacement function, the total potential energy is expressed explicitly following the thin-walled shell theory. The nonlinear equilibrium equations are calculated by the variation of the potential energy function, and the critical buckling pressure is predicted analytically. The verification is taken by the numerical simulation that traces the pre- and post-buckling equilibrium paths, indicating that the numerical results are in good accordance with the analytical predictions. It is found the temperature rise increases the thermal upward displacement, which is beneficial to the buckling pressure, and reduces Young's modulus, which is unbeneficial to the buckling pressure. Therefore, the buckling pressure is nonlinear to the temperature rise. Finally, a series of parametric evaluations are mainly focused on the effects of volume fraction exponent and temperature rise on the distributions of hoop strain, stress, force and bending moment.